A 'Wild West' of trade? African women and men and the gendering of globalisation from below in Guangzhou. Issue 5 (2nd September 2016) - Tu Huynh, T.
Abstract : Based on fieldwork in Guangzhou, this paper documents the activities of a group of African women traders, highlighting their role in constituting globalisation from below or a counterhegemonic globalisation that emanates from China. It further builds on previous studies on women and development to show how neoliberal economic changes in Africa since the 1980s have forced African men into the traditionally feminine role of (informal) traders between Africa and China. Struggles for economic power between African women and men traders and representations of gender in such struggles as well as the construction of a hyper-masculine discourse in the Guangzhou context are analysed in discussing how women and men are engaged in a continual process of 'making gender make sense' outside of Africa.